2014
DOI: 10.4304/jcp.9.2.441-446
|View full text |Cite
|
Sign up to set email alerts
|

Email Hoax Detection System Using Levenshtein Distance Method

Abstract: Hoaxes are non-malicious viruses. They live on deceiving human's perception by conveying false claims as truth. Throughout history, hoaxes have actually able to influence a lot of people to the extent of tarnishing the victim's image and credibility. Moreover, wrong and misleading information has always been a distortion to a human's growth. Some hoaxes were created in a way that they can even obtain personal data by convincing the victims that those data were required for official purposes. Hoaxes are differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 10 publications
0
11
0
8
Order By: Relevance
“…In addition, misinformation and misleading information has always been a deviation to human growth. Some hoaxes are created in a way that they can even obtain personal data by assuring the victims that the data is required for official purposes [26].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, misinformation and misleading information has always been a deviation to human growth. Some hoaxes are created in a way that they can even obtain personal data by assuring the victims that the data is required for official purposes [26].…”
Section: Resultsmentioning
confidence: 99%
“…Some hoaxes are made in such a way that they can be private data provided they are required for official purposes, The research proposed developing a hoax detection system by incorporating text matching method using Levenshtein Distance measure, The proposed model is used to identify text-based hoax emails. Sensitivity and specificity are used to evaluate the accuracy of the system in identifying hoax emails [3]. In 2017, Eugenio Tacchini, et al found the problem of social networking sites (SNSs) that had been about the hoaxing of information sharing by users very freely and in this study about posts can be classified as hoaxes or non-hoaxes with high accuracy [5].…”
Section: Related Studiesmentioning
confidence: 87%
“…Hoax on email is one form of attack in the cyber world where an email account will be sent with fake news that has many goals to take advantage or raise the rating of sales of a product, which would be good news hoax via email will be made the recipient panic, then the recipient will be led to forward the email containing the hoax, the trick usually use the media group or mailing list to facilitate its spread [2]. According to research conducted by Chen, Yong and Ishak, the definition of hoax is misleading and malicious information because it can alter human perception by conveying false information as important news as true news [3,4]. A Hoax can affect many people by damaging the credibility of the image of a person or group.…”
Section: Introductionmentioning
confidence: 99%
“…Hoaks dianggap sangat berbahaya karena menyebarkan informasi yang menyesatkan (Chen, Yong, & Ishak, 2014). Pemberian informasi bertujuan hanya untuk menipu dan merekayasa pembaca untuk dapat mempercayai sebuah berita.…”
Section: Diskursus Al-qur'an Tentang Hoaks 31 Hoaksunclassified